As Diferentes Representações Sociais Do Consumo De Álcool Entre Adolescentes - Yamauchi, Luciane Maya [UNIFESP] (2017)
The recurrent and early alcohol use among adolescents has been the subject of several studies, since they show that the early consumption increases the chances for a future dependence, besides several other cognitive and social damages. OBJECTIVES: Understand the different social representations of adolescents about alcohol use and to identify possible variables that may influence the construction of these representations, namely: adolescents' use of the substance and sociodemographic aspects - such as age, gender, social level, etc., with the purpose of generating data and analysis that can help in the programs of prevention of the use of drugs. METHODS: A questionnaire was applied to 386 students from the 7th grade of Elementary School to the 3rd grade of High School, from 2 private schools and 3 public schools from the South Zone of São Paulo city. For the data collection, a questionnaire was applied containing: 1. Sociodemographic profile questions; 2. Substance use frequency table and area 1 of the DUSI (Drug Use Screening Inventory); 3. Word Evocation Questionnaire. For the descriptive statistical analysis, the software R was used; for the analysis of Social Representations, Vergès Prototypic Analysis (AP) was performed, which consists of discriminating freely evoked words from a term inductor, in the case: "What comes to mind when talking about alcoholic beverages", Considering the evocation frequency of the word (F) and the mean order of recall (OME); the similarity analysis was used to confirm the centrality of the words, with the last two analyzes being carried out through IRAMUTEQ software. RESULTS: We recorded 1930 evocations with mention of 586 different words. The salient elements identified as being more susceptible to compose the Central Nucleus were "Cerveja" and "Festas", and added to the organizing elements of the similarity analysis that were "Festas" and "Adolescência", having a strong connection with the words "Amigos", "Diversão" and "Zoeira". It was observed that beer was the drink most consumed by this population, always being linked to the image of parties, joy and satisfaction, expressing positive aspects regarding the use, such as sociability and relaxation. CONCLUSION: It was concluded with the results that the consumption of alcoholic beverages is still considered common in Brazilian daily life. This fact tends to be more common in the absence of a consensus on the consumption of the drink, since it is freely propagated as something common among adolescents. Given the numerous damages that alcohol consumption can cause, especially in this phase of life, it is believed that a greater focus is needed on prevention programs to this drug, and especially, the postponement of its first contact.